Cutaneous signs of immunodeficiency - Hood, Antoinette F.; Marion & Roberta Sulzberger Institute for Dermatologic Communication and Education; American Academy of Dermatology. Committee on Audiovisual Education ([Evanston, Ill.] : American Academy of Dermatology, Committee on Audiovisual Education, 1987)
(Producer) A collection of clinical photographs involving primary and acquired immunodeficiencies (AIDS)
'From the collection of Antoinette F. Hood.'
Keywords: Acquired immunodeficiency syndrome -- Complications; Immunologic Deficiency Syndromes -- complications; Skin Diseases -- etiology; Skin diseases -- Immunology